PENYALAHGUNAAN PENGELOLAAN DANA DESA DALAM PERSPEKTIF HUKUM PIDANA - Tumuhulawa, Erwis; Tumuhulawa, Arifin; W. Amu, Roby (At-Tanwir Law Review, 2024)
This study aims to examine and analyze the Misuse of Village Fund Management in the Criminal Law Perspective and analyze Efforts to Prevent Misuse of Village Fund Management in the Criminal Law Perspective. The research method used is normative research, namely legal research conducted by means of literature review and review of legislation. The results showed that the misuse of village fund management in the perspective of criminal law is embezzlement, misuse of budget, abuse of authority, illegal levies, mark ups, fictitious reports, budget cuts and bribes. And there are five points prone to corruption in the village fund management process that are generally carried out by village governments, namely the planning process; Accountability process; Monitoring and evaluation process; Implementation process; The process of procurement of goods and services in terms of distribution and management of village funds. Efforts to Prevent Misuse of Village Fund Management in the Perspective of Criminal Law, namely by recognizing the Mode of Corruption to strengthen the control function of all element